Weightbearing CT Analysis of the Transverse Tarsal Joint During Eversion and Inversion. (January 2022) - Rowe, Nicholas; Robertson, Cassandra E.; Singh, Stuti; Campbell, John T.; Jeng, Clifford L.
Background: Understanding of the movement and function of the transverse tarsal joint (TTJt) continues to evolve. Most studies have been done in cadavers or under nonphysiologic conditions. Weightbearing computed tomographic (WBCT) scans may provide more accurate information about the position of the TTJt when the hindfoot is in valgus or varus. Methods: Five volunteers underwent bilateral weightbearing CT scans while standing on a platform that positioned both hindfeet in 20 degrees of valgus and 20 degrees of varus. Each bone of the foot was segmented, and the joint surfaces of the talus, calcaneus, cuboid, and navicular were identified. The principal axes for each joint surface were determined and used to calculate the angles and distances between the bones with the foot in valgus or varus. Results: In the coronal plane, the angle between the talus and calcaneus rotated 17.1 degrees as the hindfoot moved from valgus to varus. The distance between the centers of the talus and calcaneus decreased 7.1 mm. The cuboid translated 3.9 mm medially relative to the calcaneus. There was no change in angle or distance between the cuboid and navicular. The navicular rotated 25.4 degrees into varus relative to the talus. Conclusion: The TTJt locking mechanism was previously thought to occur from the talonavicular and calcaneocuboid joint axes moving from parallel to divergent as the hindfoot inverts. The current data show a more complex interaction between the four bones that comprise the TTJt and suggests that the locking mechanism may occur because of tightening of the ligaments and joint capsules. Clinical relevance: This study uses weight bearing CT scans of healthy, asymptomatic volunteers standing on valgus and varus platforms to characterize the normal motion of the transverse tarsal joint of the foot. A better understanding of how the transverse tarsal joint functions may assist clinicians in both the conservative and surgical management of hindfoot pathology.